Energy and diplomacy - Khosla, I. P.; Association of Indian Diplomats; India International Centre (Delhi Konark Publishers, 2005)
Contributed articles presented at a seminar in 2005 on natural gas pipeline imports in India.
"Association of Indian Diplomats, New Delhi in association with India International Centre, New Delhi."
Keywords: Natural gas pipelines -- India; Natural gas pipelines -- Iran; Energy policy -- India -- International cooperation; Natural gas -- Transportation -- Political aspects -- India